2022
DOI: 10.1080/10106049.2022.2043451
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing of land use-land cover change and climate variability on hydrological processes in Sub-Saharan Africa: key scientific strides and challenges

Abstract: The impact of land use land cover (LULC) change and climate variability on water resources poses as a major threat in semi-arid environments, especially in the sub-Saharan Africa. Countries in sub-Saharan Africa are vulnerable to water scarcity. Hence, there is an urgent need for understanding the various methods for LULC change and climate variability assessment, to aid in water resources management at various scales. Various studies have modelled and assessed the effect of LULC change and climate variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 123 publications
0
6
0
Order By: Relevance
“…First, it can contribute to a better understanding of the various socioeconomic and environmental elements that conduce to flood risk [25]. For example, SH can be employed to investigate how land use changes, urbanization, and population increase influence the frequency and severity of floods, as well as how these variables interact with natural elements like climatic volatility and extreme weather events [26]. Second, SH may assist in identifying the social and economic consequences of floods, as well as how these consequences are dispersed among various areas and groups [27].…”
Section: Application Of Sh To Flood Management?mentioning
confidence: 99%
“…First, it can contribute to a better understanding of the various socioeconomic and environmental elements that conduce to flood risk [25]. For example, SH can be employed to investigate how land use changes, urbanization, and population increase influence the frequency and severity of floods, as well as how these variables interact with natural elements like climatic volatility and extreme weather events [26]. Second, SH may assist in identifying the social and economic consequences of floods, as well as how these consequences are dispersed among various areas and groups [27].…”
Section: Application Of Sh To Flood Management?mentioning
confidence: 99%
“…Urban areas are fast experiencing the effect of climatic changes with the accumulation of greenhouse gases (GHGs) owing to the daily economic activities and industrial processes that proliferate the increase of GHGs (Georgescu et al, 2021). In Sub-Saharan Africa, urban areas are experiencing extreme climate indices from intense flooding to urban heat islands (UHI), affecting the human population (Govender et al, 2022). The term "urban heat island" (UHI) refers to the phenomenon in which cities have warmer air and surfaces than their surrounding rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of LULC is to more thoroughly understand the continuous variation of LULC in the region, and its essence is to explain the interaction between people and the environment. In some developing countries and Africa, there are few studies on comprehensive evaluation of the driving force analysis and results of land use change [12,13]. Research in recent years has mainly focused on some underdeveloped areas in Asia and Africa, and the results have shown that land cover has decreased due to population growth, economic development, and globalized human activities [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%